STIKER EDUKASI KESEHATAN UNTUK MENINGKATKAN PSYCHOLOGICAL WELL BEING POSYANDU LANSIA DESA WRINGIN PUTIH KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Haq, Akhmad Liana Amrul; Yulita, Destri Safitri; Nofiana, Ida; Prihatini, Rahmawati Ayu (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Psychological well-being is important to do because the positive value comes from mental health in a person can identify what is missing in his life. The impact of psychological well-being on the health and productivity of the elderly shows how important high psychological well-being is for the elderly. This study uses a research method. The research location is Jetis Gayu Hamlet, Wringinputih, Borobudur. The collection of research data was obtained from an interview process between the Head of Jetis Gayu Hamlet and students of the Muhammadiyah University of Magelang. The data obtained from the interview and observation processes will be presented descriptively using words that are easy to understand and understand. The results of the study as a whole show that health education stickers can increase the knowledge of the elderly about the importance of seeking treatment and health checks, and can increase the interest of the elderly in the benefits and existence of posyandu.